Preparation of Cerium Oxide Nanoparticles and Their Cytotoxicity Evaluation In vitro and In vivo - Zandi, Milad; Fazeli, Maryam; Bigdeli, Razieh; Asgary, Vahid; Ahangari Cohan, Reza; Bashar, Rouzbeh; Shahmahmoodi, Shohreh (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Nanotechnology plays a significant role in medicine, especially in diagnosis and treatment as a carrier to drugs and vaccinology. Several studies were conducted using nanoparticles as an adjuvant. The main aim of this study was in vivo and in vitro toxicity evaluation of synthesized Cerium Nanoparticles (CeNPs). Methods: In the present study, cerium nanoparticles were prepared using the wet chemical method. The formation of cerium nanoparticles was confirmed by scanning electron microscopy, transmission electron microscopes, x-ray diffraction analysis, dynamic light scattering. In vivo and in vitro toxicity of synthesized nanoparticles was evaluated in three different amounts of cerium nanoparticles (30 µg, 50 µg, & 100 µg) in mice and human fibroblast cell lines, respectively. Results: Cerium nanoparticles were successfully synthesized, and the identity was confirmed by x-ray diffraction analysis. The shape and size of nanoparticles were spherical. The prepared nanoparticles had a charge of -26.6 mV and a hydrodynamic radius of 446 nm. MTT assay indicated that none of the concentration of cerium was toxic, and in vivo toxicity also clarified the safety of cerium nanoparticles in mice; no significant un-normal behavioral and physical symptoms were observed in mice after CeNP administration Conclusion: Cerium nanoparticles have special properties, especially low toxicity, unique capabilities in stimulating the immune system. Cerium nanoparticles can be considered an effective and safe candidate in vaccines.